MODEL PENGEMBANGAN AGROTEKNOPRENEURSHIP PADA AGRIBISNIS KENTANG DI KABUPATEN BENER MERIAH - Lukman Hakim (Jurnal Agrisep, 2016)
This research aimed to design a model of agrotechnopreneurship in the development of agribusiness potatoes in an effort to increase revenue and bargaining position of farmers in Bener Meriah District. The method applied to achieve these objectives is the methodology of system dynamics. Potatoes production centers in Aceh Province, namely Bener Meriah District, were chosen to be the working area of the study. Identification of the need for agrotechnopreneurship model done through literature and interviews with experts from stakeholders, namely practitioners and policy makers involved in the procedure of input supply, production, and marketing of potatoes output. Data collected consisted of primary and secondary data. The primary data obtained through observation, discussion and in-depth interviews with respondents, while secondary data obtained through the study of literature from various sources of literature, books, scientific journals, and a variety of publications related to this research. Formulation of model made by software Veneta Simulation (Vensim PLE), followed by simulation. The result of this research showed that the higher the market opportunities and farmer returns, the higher the motivation of new entrepreneurs in investing, and after adding a number of farmers competent scenarios, showed an increase in production of potatoes farmers.